2020
DOI: 10.21203/rs.3.rs-127138/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First Isolation and Genotyping of Toxoplasma Gondii Strains From Domestic Animals in Tunisia

Abstract: The isolation and molecular typing of Toxoplasma gondii strains provides an essential basis for a better understanding of the distribution of genetic diversity and associated human health risks. In this context, we report, the molecular characterization of strains of T. gondii isolated from domestic animals infected with T. gondii in Southern and coastal area of Tunisia. This diversity is compared to that known for the Western European and Mediterranean sub-region.Blood, hearts and/or brains were collected fro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…This is therefore the first record of the Africa 4 lineage in the region. This lineage is widespread in Africa (Egypt, Ethiopia, Senegal, Mali, Ghana, Benin, Gambia and Tunisia) and has also been reported in several Asian countries (China, Sri Lanka, United Arab Emirates) (Galal et al, 2018;Galal et al, 2019a;Galal et al, 2019b;Hamidovićet al, 2021;Lachkhem et al, 2021). Our results therefore revealed a wider distribution area of the Africa 4 lineage across the African continent.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This is therefore the first record of the Africa 4 lineage in the region. This lineage is widespread in Africa (Egypt, Ethiopia, Senegal, Mali, Ghana, Benin, Gambia and Tunisia) and has also been reported in several Asian countries (China, Sri Lanka, United Arab Emirates) (Galal et al, 2018;Galal et al, 2019a;Galal et al, 2019b;Hamidovićet al, 2021;Lachkhem et al, 2021). Our results therefore revealed a wider distribution area of the Africa 4 lineage across the African continent.…”
Section: Discussionsupporting
confidence: 77%
“…Our results therefore revealed a wider distribution area of the Africa 4 lineage across the African continent. With the presence of the Type II lineage and now the Africa 4 lineage, the diversity in South Africa may be similar to that observed in North and East Africa, even though the Type III lineage described in these regions has not yet been found in South Africa (Galal et al, 2018;Lachkhem et al, 2021). A recent study showed that T. gondii lineages from the Old World (Africa, Asia and Europe), including the Africa 4 lineage, would be better adapted to the domestic environment, with a better potential for the sexual reproduction efficiency of these strains in the domestic cat (Galal et al, 2022).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation